Use of a bovine simulator for transrectal palpation practices - Baracaldo-Martinez, Andrea (2019)
The aim of this study was to determine the efficiency of a bovine simulator for transrectal palpation practices. A commercial bovine simulator and four non-pregnant bovine females were used. The study included 20 and 22 students without experience in transrectal palpation who participated in the experimental (I) and control (II) group, respectively. The students of group I were trained with the simulator for the location of cervix, uterus and ovaries, while those of group II received a traditional practice, consisting of working with reproductive tracts in situ. Then, both groups were evaluated by two expert instructors in four cows regarding the correct location of the anatomical structures. The Chi square test determined differences in the degree of accuracy of the recognition of the anatomical structures between groups (p<0.05), having a better level of recognition of the structures in the experimental group, which indicated the utility of the simulator for the identification of the cervix, uterus and ovaries in transrectal palpation practices.